The Role of Youth in Achieving the Sustainable Development Goals (SDGs) - Nasrullah Nasrullah (Al-Irfan : Journal of Arabic Literature and Islamic Studies, 2022)
Youth is an important asset of a country. The role of the youth is very important because it is the youth who will continue the struggle of the predecessors of the Indonesian nation. However, with the rapid technological development changes and its current sophistication, not a few young people today are dissolving the negative side of technological progress. For this reason, government intervention is needed in making programs that can increase the potential of Indonesia's young generation. One of the programs launched by the government is the Sustainable Development Goals or known by the acronym SDGs. Through this Sustainable Development Goals program, the state hopes that the programs that have been launched are not stagnant or can be sustainable and even develop and adapt to the times. Based on its objectivity, what is the Role of Youth in Achieving the SDGs Program? And what is the role of the government in increasing or optimizing the role of youth in achieving the SDGs program? To find out the problems above, a research approach was carried out. This study uses a library research approach. Based on the data obtained, it is known that the role of youth today is as Agent of Change, Agent of Development, Agent of Modernizations, Education Development, and high fighting spirit. This study uses a library research approach. Based on the data obtained, it is known that the role of youth today is as Agent of Change, Agent of Development, Agent of Modernizations, Education Development, and high fighting spirit. Meanwhile, the government's role is present in various programs to achieve the SDGs, which consist of 17 programs. To achieve these 17 programs, the government is present starting by providing training, workshops, educational seminars, or mentoring for youth who are struggling in the MSME sector, and others. This is to increase the potential of youth in order to realize the ideals of the nation.